Chinese herbal formula in the treatment of metabolic dysfunction-associated steatotic liver disease: current evidence and practice - Tao, Shao-Hong; Lei, Yu-Qing; Tan, Yi-Mei; Yang, Yu-Bo; Xie, Wei-Ning (Frontiers in Medicine, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as nonalcoholic fatty liver disease, continues to rise with rapid economic development and poses significant challenges to human health. No effective drugs are clinically approved. MASLD is regarded as a multifaceted pathological process encompassing aberrant lipid metabolism, insulin resistance, inflammation, gut microbiota imbalance, apoptosis, fibrosis, and cirrhosis. In recent decades, herbal medicines have gained increasing attention as potential therapeutic agents for the prevention and treatment of MASLD, due to their good tolerance, high efficacy, and low toxicity. In this review, we summarize the pathological mechanisms of MASLD; emphasis is placed on the anti-MASLD mechanisms of Chinese herbal formula (CHF), especially their effects on improving lipid metabolism, inflammation, intestinal flora, and fibrosis. Our goal is to better understand the pharmacological mechanisms of CHF to inform research on the development of new drugs for the treatment of MASLD.